Caring Nurse Services Increase Patient Satisfaction in the Catheterization Room - Ginting, Apri Chandra Putra; Saputra, Rangga; Haeriyah, Siti (Universitas Muhammadiyah Semarang, 2024)
Background: The nursing profession's caring service is one of the indicators of success in determining patient satisfaction which will have an impact on the quality of customer satisfaction in the health facility.Objective: The purpose of the study is to determine the relationship between caring nurse services and patient satisfactionMethods: Correlational descriptive with a cross sectional approach. Results: The results of the univariate analysis showed that caring nurse services were sufficient (53.3%) in the Catheterization Room of EMC Alam Sutera Hospital, South Tangerang City and most patients said they were satisfied (56.7%) with caring care services. The results of the bivariate analysis show that there is a strong relationship between caring nurse services and patient satisfaction in the Catheterization Room of EMC Alam Sutera Hospital, South Tangerang City in 2022 (p value: 0.001, correlation 0.579).Conclusion: There is a strong relationship between caring nurse services and patient satisfaction in the Catheterization Room of EMC Alam Sutera Hospital, South Tangerang City